2012
DOI: 10.3109/0886022x.2012.723662
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition ofPAX2Gene Expression by siRNA (Polyethylenimine) in Experimental Model of Obstructive Nephropathy

Abstract: Objective: It was found that PAX2 (Paired Box 2) re-expression in renal tubular epithelial cells correlated with renal interstitial fibrosis of rats with obstructive nephropathy. The purpose of the present study was to identify whether RNA interference (RNAi) induced by polyethylenimine (jetPEI) could inhibit PAX2 gene re-expression and impact renal interstitial fibrosis of rats with obstructive nephropathy. Methods: Four pairs of small interfering RNA (siRNA) interference sequences and a negative control were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…Polyethylenimine (PEI) nanoparticles, liposome nanoparticles, and cationic gelatin nanoparticles have been demonstrated to show effective delivery of genes to the kidney and have promising treatment effects in animal models of renal fibrosis [4954]. …”
Section: Viral and Non-viral Vectors For Renal Fibrosis In Vivomentioning
confidence: 99%
See 3 more Smart Citations
“…Polyethylenimine (PEI) nanoparticles, liposome nanoparticles, and cationic gelatin nanoparticles have been demonstrated to show effective delivery of genes to the kidney and have promising treatment effects in animal models of renal fibrosis [4954]. …”
Section: Viral and Non-viral Vectors For Renal Fibrosis In Vivomentioning
confidence: 99%
“…Small interfering RNA (siRNA) targeted paired box2 (PAX2) was reported to be delivered to the kidney with PEI nanoparticles via an intrarenal capsule injection in a mouse model of renal fibrosis induced by UUO [49]. PAX2–siRNA–PEI nanoparticles inhibited PAX2 mRNA and PAX2 protein in the kidney, and ameliorated renal fibrosis [49].…”
Section: Viral and Non-viral Vectors For Renal Fibrosis In Vivomentioning
confidence: 99%
See 2 more Smart Citations
“…PAX2 is not expressed in mature kidneys, but it is expressed following renal injury [5] . Our preliminary study indicated that PAX2 can causes RIF via EMT [6,7] , and we subsequently found that PAX2 could induce EMT in normal renal tubular epithelial cells in vitro [8] , which indicates that PAX2 is associated with the development of RIF. However, the mechanisms involved in how PAX2 induces EMT are not well understood.…”
Section: Introductionmentioning
confidence: 99%